2017
DOI: 10.18805/lr.v0i0.7023
|View full text |Cite
|
Sign up to set email alerts
|

Seed quality enhancement through seed priming in pigeonpea [Cajanus cajan (L.) Millsp.]

Abstract: ABSTARCTExperiment was conducted in the Seed Testing Laboratory during 2013 and 2014 at RARS, UAS Campus, Vijayapur, Karnataka State. The seeds were primed by soaking in different leaf extracts and chemical solution for one hour and then decanted the extracts and seeds were air dried under the shade to bring back to their original moisture content and used for seed quality studies. Seed germination was significantly influenced by age of the seeds and its interaction with botanicals and chemicals. Among the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Compared to unprimed seeds (control) except treatment T 5 (nutripriming with ZnSO 4 0.025 per cent + borax 0.01 per cent), the other treatments recorded higher germination per centage, germination index, speed of germination and mean daily germination. The result is in conformity with the findings of Farooq et al (2007) and Sajjan et al (2017) who observed that the seed priming enhanced the germination rate, better allometric attributes, faster emergence of seedlings as well as early germination. Faster emergence of primed seeds might be due to metabolic repair during imbibition (Bray et al, 1989) and build of germination enhancing metabolites (Basra et al, 1995), while higher and synchronized emergence was the consequence of reduced physiological non-uniformity in the seeds due to priming (Juraimi et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Compared to unprimed seeds (control) except treatment T 5 (nutripriming with ZnSO 4 0.025 per cent + borax 0.01 per cent), the other treatments recorded higher germination per centage, germination index, speed of germination and mean daily germination. The result is in conformity with the findings of Farooq et al (2007) and Sajjan et al (2017) who observed that the seed priming enhanced the germination rate, better allometric attributes, faster emergence of seedlings as well as early germination. Faster emergence of primed seeds might be due to metabolic repair during imbibition (Bray et al, 1989) and build of germination enhancing metabolites (Basra et al, 1995), while higher and synchronized emergence was the consequence of reduced physiological non-uniformity in the seeds due to priming (Juraimi et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Seed priming ensures increased and uniform germination by reducing the imbibition time [27], increasing the pre-germinative enzyme activation, increasing metabolite production [28], repairing the damaged DNA [29], and regulating osmosis. There are many reports on seed priming toward improving seed germination, seedling emergence, stand establishment, crop growth, nodulation, and productivity in various crop species viz., rice [30][31][32], wheat [33,34], pulses [35][36][37][38][39][40][41], okra [42], Chinese cabbage [43], sunflower [44], and melons [45]. Seed priming induces antioxidant activity and storage protein solubilization and minimizes lipid peroxidation [46].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the individual seed also plays a major role in the seed germination quality. Large sized seeds in pigeon pea recorded a higher percentage of germination and field emergence [ 16 , 17 , 18 ]. These properties are affected by numerous factors such as size, form, moisture content of the grain [ 19 ] and varieties [ 20 ].…”
Section: Introductionmentioning
confidence: 99%